2011
DOI: 10.1007/s10029-011-0804-2
|View full text |Cite
|
Sign up to set email alerts
|

Elastic fibers in the anterior abdominal wall

Abstract: It is essential to analyze the anterior abdominal wall concerning its anatomical condition and histological components. Altered collagen and elastic fibers play an important role in hernia formation, indicating that the main factor may be biological.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Elastin gives tissues in the human body elasticity. Fachinelli et al [15] reported that a significant higher amount of elastin is found in the abdominal wall in patients with ventral hernias. These findings suggest that not only anatomical diversity but also microscopic and histological factors plays a role in the acquirement of epigastric hernias.…”
Section: Microscopic Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Elastin gives tissues in the human body elasticity. Fachinelli et al [15] reported that a significant higher amount of elastin is found in the abdominal wall in patients with ventral hernias. These findings suggest that not only anatomical diversity but also microscopic and histological factors plays a role in the acquirement of epigastric hernias.…”
Section: Microscopic Studiesmentioning
confidence: 98%
“…Recent microscopic anatomical studies show that not only the macroscopic anatomy of the linea alba is important in epigastric hernia pathology, but that the microscopic aspects should also be considered [14,15]. Degeneration of collagen is associated with the requirement of several ventral hernias [14,16].…”
Section: Microscopic Studiesmentioning
confidence: 99%
“…In a combination of epigastric, incisional, and umbilical hernias, the amount of elastin was significantly increased although the structure of the elastic fibers was altered, demonstrating a fragmented, thickened shape in patients with ventral hernia. 26 …”
Section: Evidence For Collagenopathies In Herniasmentioning
confidence: 99%
“…There has been research to suggest that patients with hernias have less type I collagen and more elastin in the linea alba than patients without hernias. 22,23 This type of connective tissue disorder is not otherwise clinically apparent, but likely predisposes certain individuals to developing a hernia. Of course, more obvious sources of trauma, such as blunt force from a motor vehicle collision or heavy blow to the abdomen, can cause a hernia as well.…”
Section: Etiologymentioning
confidence: 99%